Methodological Basis for the Strategic Analysis of Development of International Hotel Chains in Russia - ZAITSEVA, Natalia A.; LARIONOVA, Anna A.; SKROBOTOVA, Olga V.; IVANOVA, Raisa M.; RADINA, Oksana I. (Journal of Advanced Research in Law and Economics, 2017)
The relevance of the research questions a strategic review of the development of international hotel chains in Russia is caused by the necessity of objective evaluation of complex, dynamic environment of the hospitality business and the identification of opportunities and threats that must be considered when making strategic decisions. The authors, for the analysis of the current situation and trends of international hotel chains’ development in Russia, used the expert assessment, methods of economic-statistical analysis. On the basis of utilization of theoretic-empirical methods and methods of modeling the model of the sequence and interrelation of basic elements of the strategic analysis of the international hotel networks’ development was worked out. In the article, the analysis of the directions of a strategic development of the international hotel networks in Russia, which allowed determining success factors of development of hotel network, is carried out. The authors suggest a model of the sequence and relationships of major elements of strategic analysis for the development of international hotel chains, which includes the study of state and prospects of development of hotel business in Russian regions, analysis of the position of the international hotel chain in a competitive environment, analysis of the operational efficiency of the company activities, the study of directions of strategic development of international hotel chains in Russia. The application of the recommendations proposed by the authors will enhance the effectiveness of the development strategy of international hotel chains in Russia through improving procedures of strategic analysis.